The Efficient Apoptotic Induction of Paclitaxel-Loaded Poly(N-vinylpyrrolidone)-block-poly(ε-caprolactone) Nanoparticles in the In Vitro Study of Lung Cancer Cell Lines. (29th June 2015) - Zheng, Donghui; Ye, Huiping; Luo, Can; Xu, Huae; Meng, Ling
Abstract : Paclitaxel (Ptx) has been established as one of the most important components of first line chemotherapy regimen in the treatment of lung cancer. However, the poor solubility of Ptx makes it employ Cremophor as a solvent, which greatly limits its application due to the severe adverse effect. Encapsulation of Ptx into nanoparticles substantially increases the solubility of Ptx, therefore eradicating the necessity of Cremophor involvement. Here we report on a simple way of preparing Ptx-loaded nanoparticles formed by amphiphilic poly(N-vinylpyrrolidone)-block-poly( ε -caprolactone) (PVP- b -PCL) copolymers. Ptx was incorporated into PVP- b -PCL nanoparticles with a high loading efficiency. In vitro release study shows that Ptx was released from the nanoparticles in a sustained manner. The following experiments including cell staining and cytotoxicity tests indicated that Ptx-NPs led to enhanced induction of apoptosis in non-small-cell lung cancer cell lines NCI-1975 and A549, which is achieved by regulating the expression of apoptosis related proteins. Therefore, data from this study offers an effective way of improving the anticancer efficiency of Ptx by a nanodrug delivery system with amphiphilic PVP- b -PCL as drug carriers.